2004
DOI: 10.1248/bpb.27.1642
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Mixed Effects Model Analysis of the Pharmacokinetics of Metoprolol in Routinely Treated Japanese Patients

Abstract: This study was performed to estimate the mean pharmacokinetic parameters of routinely administered metoprolol in middle-aged and elderly Japanese patients. Whole blood concentration data (65 samples) at steady-state following repetitive administration to 34 patients were analyzed using a nonlinear mixed effects model. A one-compartment model was parameterized in terms of oral clearance (CL/F) and apparent volume of distribution (V/F). We evaluated the effect of polymorphic alleles (CYP2D6*2, CYP2D6*10, CYP2C19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 36 publications
(48 reference statements)
3
44
0
1
Order By: Relevance
“…13,14) 15) That is, Group 1 consisted of extensive metabolizers with CYP2D6*1/*1, *1/*2, and *2/*2; Group 2 consisted of subjects with CYP2D6*1/*5, *1/*10, *2/*5, *2/*10, and *2/*41; and Group 3 consisted of subjects with CYP2D6*5/*10, *10/*10, and *41/*41 (Table 1). 15,16) In addition, subjects heterozygous for CYP2D6*2/*41 and homozygous for CYP2D6*41/*41 were classified into Group 2 and Group 3, respectively, since it was reported that the CYP2D6*41 allele may be associated with the intermediate metabolizer phenotype. 16,17) In the single-dose (protocol 1) trial, each subject received a single dose of 6 mg aripiprazole (ABILIFY ® tablet) under a fasting condition.…”
Section: Pharmacokinetic Datamentioning
confidence: 99%
“…13,14) 15) That is, Group 1 consisted of extensive metabolizers with CYP2D6*1/*1, *1/*2, and *2/*2; Group 2 consisted of subjects with CYP2D6*1/*5, *1/*10, *2/*5, *2/*10, and *2/*41; and Group 3 consisted of subjects with CYP2D6*5/*10, *10/*10, and *41/*41 (Table 1). 15,16) In addition, subjects heterozygous for CYP2D6*2/*41 and homozygous for CYP2D6*41/*41 were classified into Group 2 and Group 3, respectively, since it was reported that the CYP2D6*41 allele may be associated with the intermediate metabolizer phenotype. 16,17) In the single-dose (protocol 1) trial, each subject received a single dose of 6 mg aripiprazole (ABILIFY ® tablet) under a fasting condition.…”
Section: Pharmacokinetic Datamentioning
confidence: 99%
“…Taguchi et al evaluated the effect of polymorphic alleles (CYP2D6*2, CYP2D6*10, CYP2C19*2 and CYP2C19*3), age, sex, and heart failure on the pharmacokinetic parameters of metoprolol. The CL/F value in patients homozygous for the CYP2D6*10 allele was 64% lower than that in patients with the CYP2D6*1/*1 or *1/*2 genotype [12]. Nozawa et al showed, that in patients routinely treated with metoprolol, the CYP2D6 genotype significantly affects circadian variations of beta-adrenergic inhibition induced by metoprolol [13].…”
Section: Resultsmentioning
confidence: 99%
“…The CYP2D6 gene is highly polymorphic with about 80 alleles reported to date [47]. Due to the polymorphic drug metabolizing enzyme, pharmacokinetics of metoprolol vary among individuals [48,49]. This may result in variable responses to the drug, particularly at therapy initiation, given the need to initiate β-blockers at low doses.…”
Section: Genetic Associations With β-Blocker Tolerability In Hfmentioning
confidence: 99%